A PARADIGM SHIFT IN EDUCATION FOR EDUCATORS INDEPENDENCE AND INNOVATION - Khalilurrahman, Khalilurrahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this study is to deepen our understanding of paradigm shifts in education and the importance of adopting an independent curriculum as an innovative solution. Through in-depth research and discussion, it is hoped that this journal can provide insight and inspiration for education practitioners, researchers and policy makers to move towards a more relevant, inclusive and adaptive education. This research method uses descriptive qualitative research case studies at schools in the Probolinggo district. Paradigm shifts in education are becoming increasingly important due to world demands that continue to grow, both in terms of economic, social, and technology. The traditional educational model, which focuses on instruction-based learning and factual knowledge, is no longer sufficient to face complex and multidimensional future challenges. Paradigm shifts in education refer to fundamental changes in the way we view and carry out the learning process. Traditional paradigms that focus on factual knowledge, academic achievement, and teacher-centred learning have proven insufficient to prepare young people for a changing world. In the era of globalization and technological revolution, the need for 21st century skills such as critical thinking, creativity, collaboration, communication and digital literacy is becoming increasingly important.